The Product Life Cycle—Analysis and Applications Issues - Shukla, Ajit Kumar (Indian Journal of Marketing, 2005)
Like a human being, a product is characterized by a life cycle, which refers to the life span of a product with several stages. All these stages are recognized and a product goes through these stages from its introduction to its abandonment. Thus, Product Life Cycle (PLC) refers to the different stages through which a product passes from introduction, through growth, maturity, to its decline and death resulting in the final withdrawal of it from the market as an eventuality. After launching the new product, management wants the product to enjoy a long and happy life. Although it does not expect the product to sell forever, management wants to earn a decent profit to cover all the effort and risk that went into launching it. The administration is aware that each product will have a life cycle, although the exact shape and length is not known in advance. Products, like consumers / tourists, go through life cycles. So product planning and marketing mix planning are important. A company’s positioning and differentiation strategy must change as the product, market, and competitors change over time.